Media Pembelajaran Interaktif Virtual Bitmoji Scene di Mi Miftahul Ulum 02 Honggosoco - Muhammad Misbahul Munir; Harminto Mulyo; Fira Nadliratul Afrida; Irma Nur Af’idah (IKIP PGRI Bojonegoro, 2023)
ABSTRACTTechnological advances involve renewal and innovation in various aspects, one of its is in learning. Technology-based interactive media need to be developed to support the learning process. In this case, the role of educators is very important in developing media. But in reality, there are still many educators who have not been able to create and innovate learning media development. This will certainly affect the learning interest of students because learning is monotonous and boring. The solution offered is based on the description of the problem, namely by assisting in the creation of technology-based interactive learning media. One of the technology-based interactive media that can be developed to improve the quality of education is Virtual Bitmoji Scene. Virtual Bitmoji Scene is an effective interactive learning media by applying animated characters that can be adapted to the age background of SD/MI students. This assistance is able to help educators create interactive learning media so that it is hoped that learning objectives will be more easily achieved. Based on the results of the mentoring and training activities carried out from the four assessed aspects, namely the understanding and skills of educators in using technology-based learning media as well as the understanding and ability of educators to create interactive learning media Virtual Bitmoji Scene, an average increase of 65.55% was obtained. . So it can be concluded that there is improvement of educators understanding and skill regarding interactive learning media based on Virtual Bitmoji Scene technology. Keywords : Technology, Interactive, Virtual Bitmoji Scene ABSTRAKKemajuan teknologi mengharuskan adanya pembaruan dan inovasi di berbagai aspek, salah satunya dalam pembelajaran. Media interaktif berbasis teknologi perlu dikembangkan untuk menunjang proses pembelajaran. Dalam hal ini, peran pendidik sangat penting dalam mengembangkan media. Namun pada kenyataannya, masih banyak pendidik yang belum mampu berkreasi dan berinovasi dalam mengembangkan media pembelajaran. Hal ini tentu akan berpengaruh pada minat belajar peserta didik dikarenakan pembelajaran yang monoton dan membosankan. Solusi yang ditawarkan berdasarkan uraian permasalahan tersebut yaitu dengan pendampingan pembuatan media pembelajaran interaktif berbasis teknologi. Salah satu media interaktif berbasis teknologi yang dapat dikembangkan untuk meningkatkan kualitas pendidikan yaitu Virtual Bitmoji Scene. Virtual Bitmoji Scene merupakan media pembelajaran interaktif yang efektif dengan menerapkan karakter animasi yang dapat disesuaikan dengan latar belakang usia peserta didik SD/MI. Pendampingan ini mampu membantu pendidik membuat media pembelajaran interaktif sehingga diharapkan tujuan pembelajaran akan lebih mudah tercapai. Berdasarkan hasil kegiatan pendampingan dan pelatihan yang dilakukan dari ke empat aspek yang dinilai, yaitu pemahaman dan keterampilan pendidik dalam menggunakan media pembelajaran berbasis teknologi serta pemahaman dan kemampuan pendidik membuat media pembelajaran interaktif Virtual Bitmoji Scene, diperoleh hasil rata-rata peningkatan sebesar 65,55%. Sehingga dapat disimpulkan terjadi peningkatan pemahaman dan keterampilan pendidik mengenai media pembelajaran interaktif berbasis teknologi Virtual Bitmoji Scene. Kata Kunci : Teknologi, Interaktif, Virtual Bitmoji Scene